Research on Characteristics of Irradiation Production of 63Ni with High Specific Activity - Jian LI; Jing ZHAO; Zhihong LIU; Wei XU; Heng XIE; Lei SHI (Journal of Isotopes)
63Ni is an important industrial radioisotope，which has the characteristics of long half-life，moderate power density and easy to manufacture. 63Ni is a promising β radiation source with low energy. The characteristics of irradiation production of 63Ni with high specific activity in high flux reactor are studied，and the influence of neutron flux，neutron energy spectrum，irradiation target design scheme on the specific radioactivity are analyzed. On this basis，the ideas of irradiation scheme design for further improving the specific activity of 63Ni are discussed. The research shows that ultra-high flux reactor helps to improve the specific activity of 63Ni. The results provide references for the irradiation production scheme design of 63Ni.